BMP6 increases CD68 expression by up-regulating CTGF expression in human granulosa-lutein cells. (1st October 2021) - Zhang, Xin-Yue; Chang, Hsun-Ming; Yi, Yuyin; Zhu, Hua; Liu, Rui-Zhi; Leung, Peter C.K.
Abstract: Bone morphogenetic protein 6 (BMP6) and connective tissue growth factor (CTGF) are critical growth factors required for normal follicular development and luteal function. Cluster of Differentiation 68 (CD68) is an intraovarian marker of macrophages that plays an important role in modulating the physiological regression of the corpus luteum. The aim of this study was to investigate the effect of BMP6 on the expression of CTGF and the subsequent increase in CD68 expression as well as its underlying mechanisms. Primary and immortalized (SVOG) human granulosa cells obtained from infertile women undergoing in vitro fertilization treatment were used as cell models to conduct the in vitro experiments. Our results showed that BMP6 treatment significantly increased the expression levels of CTGF and CD68. Using BMP type I receptor inhibitors (dorsomorphin, DMH-1 and SB431542), we demonstrated that both activin receptor-like kinase (ALK)2 and ALK3 are involved in BMP6-induced stimulatory effects on the expression of CTGF and CD68. Additionally, SMAD4-knock down reversed the BMP6-induced up-regulation of CTGF and CD68, indicating that the canonical SMAD signaling pathway is required for these effects. Moreover, CTGF-knock down abolished the BMP6-induced up-regulation of CD68 expression. These findings indicate that intrafollicular CTGF mediates BMP6-induced increases in CD68 expression through the ALK2/ALK3-mediated SMAD-dependent signaling pathway. Highlights: BMP6 significantly increases the expression levels of CTGF and CD68. ALK2 and ALK3 are involved in BMP6-induced upregulation of CTGF and CD68. SMAD signaling pathway mediates BMP6-induced upregulation of CTGF and CD68. Intrafollicular CTGF mediates BMP6-induced increases in CD68 expression.